PENERAPAN BUDAYA LITERASI MEMBACA DAN MENULIS MELALUI PEMBELAJARAN MATERI KEANEKARAGAMAN FLORA DAN FAUNA BERBANTUAN MEDIA PABALOFA PADA PESERTA DIDIK KELAS V SD NEGERI KALIBANTENG KIDUL 03 SEMARANG - Cut Dinna Puspa Kartikasari Dinna; Panca Dewi Purwati (LPPM Universitas Cipta Mandiri, 2024)
Based on the fact that the author found that in PPL I in SD State Kalibanteng Kidul 03 Semarang, inclass V B there were some pupils who did not read smoothly and could not develop writing skills to themaximum. Besides, in the class, literacy programs like the habit of reading books 15 minutes beforelearning no longer run, and the wall magazine (Mading) that is in class V B is empty without any workdisplayed. In response to these challenges, researchers propose innovative solutions by implementing aliteracy culture that emphasizes reading and writing in the classroom setting. Thus, this research aimsto describe the application of literacy culture reading and writing through material learning of thediversity of flora and fauna with the help of Pabalofa media in the students of grade V SD StateKalibanteng Kidul 03 Semarang. The research methods used in this research are qualitative descriptive methods, and the data collection techniques used are observations, interviews, and library/documentation studies. The results of this research show that through the application of literacyculture reading and writing to learning material diversity of flora and fauna aided media Pabalofa wasable to improve cognitive abilities, train the reading, writing, and speaking skills of students in grade VSD State Kalibanteng Kidul 03 Semarang.